Agresivitas Pajak, Audit Delay dan Pergantian Auditor - Sasa Sabilla; Erinos NR (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to analyze the effect of tax aggressiveness and audit delay on auditor switching. The data used in this study are financial reports consumer goods listed on the Indonesia Stock Exchange for the 2016-2019 period. The data sampling method used purposive sampling method, based on certain criteria obtained a sample of 108 company data. Auditor switching is measured by a dummy variable. The type of data used in this study is secondary data obtained from the IDX website and the website of the company concerned. Testing the hypothesis of this study using logistic regression analysis. The results show that tax aggressiveness has a positive effect on auditor switching, while audit delays have no effect on auditor switching.